(untitled) (UNED Research Journal, 2016)
The gecko Hemidactylus frenatus reached Coco’s Island on boats. We captured 21 individuals and found that their snout-cloaca length ranged from 22,30mm to 47,85mm (0,1 g to 3,6 g).